GEOLOGI DAERAH MAEN DAN SEKITARNYA, KECAMATAN LIKUPANG TIMUR, KABUPATEN MINAHASA UTARA SULAWESI UTARA - Momongan, A.J.; Moningka, M.M.; Perangin Angin, P (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2024)
Administratively, the research location is situated in the Maen area and its surroundings, Likupang Timur District, North Minahasa Regency, North Sulawesi, with UTM (Universal Transverse Mercator) coordinates 51 N 732393 mE – 736394 mE and 179973 mN – 183983 mN using the WGS 1984 datum. The research area covers an area of 4x4 square kilometers. Maen village is located in an area rich in energy and mineral resources potential. Previous geological mapping in this area was conducted on a regional scale. Therefore, the author is interested in conducting detailed mapping at a 1:10,000 scale in the Maen area and its surroundings, Likupang Timur District, North Minahasa Regency, North Sulawesi. The geomorphology of the research area comprises four geomorphological units: Piroclastic Flow Ridge unit, Lava Flow Ridge unit, Coastal Plain unit. The stratigraphy in the research area consists of four rock units arranged from oldest to youngest: Coarse Tuff unit, Lapilli Stone unit, Andesite unit, and Lake Deposit unit. The geological structure in the research area includes weathered joint fractures oriented generally northeast to southwest. Geological history in the research area began in the Pliocene epoch with the deposition of the Coarse Tuff unit, followed by the deposition of the Lapilli Stone unit in the Pleistocene epoch, and simultaneous deposition of the Andesite unit in the same Pleistocene period. The topmost layer consists of Alluvial Deposit unit deposited from the Holocene epoch to the present.